Shear wave elastography for assessing rectus femoris stiffness: a study on the interaction and reliability of body position and contraction state - Wang, Yating; Wang, Tianqi; Liu, Xuemei; Liu, Xiaona; Li, Ling; Ge, Huiyu (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveTo employ shear wave elastography (SWE) to assess changes in stiffness and reliability in the vastus rectus muscle of healthy adults across different posture-contraction states. We analyzed the main effects and interactions of posture and contraction intensity on shear wave velocity (SWV) and explored its relationship with relevant biological parameters.MethodsWe recruited healthy participants, with two observers using SWE technology to measure the SWV of the vastus rectus muscle in the supine (relaxation, plantarflexion, and dorsiflexion) and sitting (relaxation, leg elevated, and 5-kg loading) positions. Intra- and interobserver reliabilities were evaluated using the intraclass correlation reliability. Repeated-measures analysis of variance was used to examine the main effects and interactions of posture and contraction state on SWV. Additionally, correlations between the SWV and rectus femoris thickness (RFthick), circumference (RFcirc), cross-sectional area (RFcsa), and contraction index (RFci) were calculated.ResultsForty-six adults (11 males and 35 females) completed the study. SWE measurements demonstrated high intra- and interobserver reliability across all conditions (ICC >0.80). Two-way repeated-measures analysis of variance revealed significant main effects of body position (F (1,45) = 58.85, P < 0.001, ηp2 = 0.567) and contraction state (F (1.76, 78.97) = 104.23, P < 0.001, ηp2 = 0.777), with a significant interaction (F (2,44) = 24.66, P < 0.001, ηp2 = 0.459). The SWV changes were more pronounced in the 5-kg load position (45.9%). Ultrasound parameters (RFthick, RFcirc, RFci) varied significantly across conditions (P < 0.05), whereas the RFcsa did not (P = 0.194). The SWV was positively correlated with specific architectural parameters, depending on posture, but not with demographic variables (P > 0.05).ConclusionThis study establishes a methodological basis for assessing the stiffness of the RF, identifying posture and contraction as key factors. Our findings underscore the need for standardized measurement and support the future application of SWE in biomechanics, sports, and rehabilitation.